Advances in corporate branding - Balmer, John M. T.; Powell, Shaun M.; Kernstock, Joachim, 1966-; Brexendorf, Tim Oliver, 1973- (Palgrave Macmillan, 2016)
This prestigious edited collection of articles from the Journal of Brand Management discusses the impact of research on our understanding of corporate brand characteristics and corporate brand management to date. A wide range of topics are covered, including franchise brand management, co-creation of corporate brands, alliance brands, the role of internal branding in the delivery of employee brand promise, and the expansion into new approaches. Advances in Corporate Branding is essential reading for those undertaking a PhD programme or by upper level students looking for rigorous academic material on the subject and for scholars and discerning practitioners, acting as 'advanced introductions'.
Keywords: Branding (Marketing); elektronické knihy; electronic books